Technologies Used in Production Systems for Santa Inês Sheep: A Systematic Review - Bezerra, Andréia Santana; Santos, Marcos Antônio Souza dos; Lourenço-Júnior, José de Brito (Frontiers in Veterinary Science, 2022)
The study identifies the number of publications that presented technologies used in the production systems of Santa Inês sheep in the last five years (2017-2021) carried out in Brazil. Therefore, the objective was to identify where we are in terms of knowledge about technologies in different fields (health, reproduction, animal breeding, behavior and welfare, nutrition and feeding, forage and pasture, carcass and meat quality, and economics and management of livestock systems). After rigorous selection, 114 studies were appointed and classified by knowledge field, and the main approaches within each theme were evaluated, pointing out research gaps. The most technologies have been in northeastern states. However, government agencies should develop public policies to disseminate techniques in rural areas because the production system in this region is still subsistence. This study highlighted the need for works that present management practices and tools that impact the improvement of animal welfare. Agro-industrial by-products have been widely used as an alternative for sheep feeding. However, economic feasibility analyses are recommended with these foodstuffs to substantiate their use as an option to reduce production costs. There is a lack of research allusive to the management of production systems, especially those related to estimates of economic feasibility indicators.